Water and Bromide Dynamics in a Soil Amended with Different Urban Composts. Issue 1 (28th January 2013) - Chalhoub, Maha; Coquet, Yves; Vachier, Pierre
Abstract : Urban waste compost additions to soil can increase soil organic matter content and improve soil physical conditions, leading to agronomic and environmental benefits. The need for information still exists to evaluate more precisely the effects of urban waste compost on soil physical properties. Three types of urban waste composts, a biowaste compost (BIO), a municipal solid waste compost (MSW), and a co‐compost of green waste and sewage sludge (GWS), were applied once every 2 yr on a loamy soil for 10 yr. The effects of the three composts on soil water and solute transport dynamics were tested. Soil water matric head and water content were monitored using tensiometers and time domain reflectometry probes, respectively. A Br − tracer experiment was also conducted to evaluate the effect of compost application on nonsorbing solute transport. Water content measurements showed that the application of composts significantly ( P < 0.05) affected soil water content in the plow layer, with average increases of 0.03 cm 3 cm −3 for the GWS and MSW compost, and 0.015 cm 3 cm −3 for the BIO compost compared with a control without organic amendment. Bromide tracing during the wetting period showed that the application of urban waste composts did not affect the soil's potential for leaching. The application of composts did reduce soil evaporation during the spring, however, which in turn favored downward Br − migration in the soil.